The Usage of Fungi in Cadmium and Maganese Remediation - Marwa, Saeed Subeh (2017)
Heavy metals are found in the soil naturally, but certain activities such as industrial processes cause an increase in the concentration of heavy metals to amounts that will become toxic to the environment. Pollution with heavy metals such as Cadmium (Cd) and Manganese (Mn) is becoming an extremely serious environmental issue that affects plants, animals and humans. In order of overcoming pollution of Cd and Mn, Bioremediation poses as one of the best techniques to remove Cd and Mn from the environment due to its ease of application and low cost. The aim of this research was to study the potential of different fungal species in bioremediating Cd and Mn. Fungi were grown in Potato Dextrose Agar (PDA) media and then cultured in Potato Dextrose Broth (PDB) with different concentrations of Cd and Mn to test the ability of the fungi to grow and resist the toxicity of the heavy metals. The rate of growth of each fungus was obtained after one week by measuring the dry weight of every fungus on each concentration of toxicity by Cd and Mn respectively. The best strain of fungi was determined based on their ability to grow in the presence of the heavy metals. A. flavus showed the significantly highest rate of growth of 0.033667±0.001 g/week at 110 ppm which means that it had the best resistance towards the high Cd toxic conditions. P. chrysogenum showed the significantly highest rate of growth of 0.068333±0.010 g/week at 500 ppm of manganese. The fungal species were able to grow with Cd and Mn due to the many mechanisms they employ to uptake heavy metals such as biosorption.